Study guides

☆☆

Q: What is the sum of b and 5?

Write your answer...

Submit

Still have questions?

Related questions

a = 5;b = 10;c = a + b;System.out.println("The sum is " + c);a = 5;b = 10;c = a + b;System.out.println("The sum is " + c);a = 5;b = 10;c = a + b;System.out.println("The sum is " + c);a = 5;b = 10;c = a + b;System.out.println("The sum is " + c);

The algebraic expression is 3(b+5).

The expression which represents half the sum of five and a number b is (b+5)/2.

a + b = 61a - b = 5âˆ´ a = 5 + bâˆ´ (5 + b) + b = 61âˆ´ 2b = 56âˆ´ b = 28âˆ´ a = 33

3(b5)

To be divisible by 36 the number must be divisible by 9 (and 4). To be divisible by 9, the sum of the digits must be divisible by 9. 5 + 5 = 10 → need an extra 8 → A + B = 8.

start input a,b,c,d,e sum=a+b+c+d+e avg=sum/5 print"average is"; avg

5(a+b)-7

It is: 5*(b+2) which is the same as 5b+10

The sum of is the total of everything being summed; the sum total. Thus the sum of a, b and c is therefore a + b + c.

1.Start 2. Input a,b,c 3. Sum = a+b+c 4. Average = sum/3 5. Output - Sum,Average 6. Stop

int mul (int a, int b) { int sum= 0; for (; b>0; --b) sum -= -a; for (; b<0; ++b) sum -= a; return sum; }

The sum of the 5 sides.The sum of the 5 sides.The sum of the 5 sides.The sum of the 5 sides.

41

You can write that as 5 / (a + b), or as a fraction, with the 5 on top, and a + b at the bottom. The actual value of this expression will depend on the values of "a" and "b".

Um, x2+3x-5=0? This is ax2+bx+c where a=1, b=3, and c=-5. The sum of the roots is -b/a so that means the sum of the roots is -3. Also, product of the roots is c/a. That means the product of the roots is -5. -3+(-5)= -8. There you have it.

Given:a + b = 2a - b = 8Then:a = b + 8∴ (b + 8) + b = 2∴ 2b = -6∴ b = -3∴ a = 5

#include<stdio.h> main() { int a,b,sum; print f("enter two numbers"); scan f("%d%d",&a&b); sum=a+b print f(the sum of a and b is %d,sum); }

b+11

(3+b)

The sum of n and 5 is n+ 5

The sum of b and 8 would be written b+8 or 8+b(commutative property of addition)

Assuming that a and b are two non-negative numbers, then their sum is a + b and the difference is |a - b|.

it's: a + b

3a+b